Helicobacter pylori-negative Peptic Ulcer - Ji Hyun Song; Sang Gyun Kim (Yong Chan Lee, 2017)
Helicobacter pylori is the most important etiology of peptic ulcer disease. With the gradual eradication of H. pylori and the increase in the use of nonsteroidal anti-inflammatory drugs, the proportion of H. pylori-negative peptic ulcers has been increasing. It is important for false negative results to be ruled out in H. pylori-negative peptic ulcers, and medical treatment for long-term maintenance should be considered because of the high risk of recurrence and related complications associated with the disease.